A poem about being bound and/or leaving? Ambivalences and paradoxes in Ady’s poem ’Sípja régi babonának’ - Czetter, Ibolya (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2020)
While rereading the poem, the paper offers an interpretation and aims to uncover a set of yet unexplored contextual connections. In the analysis the components of the linguistic shaping of the text are foregrounded. In the process of re-reading, several interrelations will be disclosed concerning Ady’s oeuvre, the genre, the theory of poetics as well as those that contribute to a more up-to-date evaluation of Ady’s poetry. The paper takes its starting point in the role paradoxiality performs in the oeuvre. Various types of paradox as well as the figurative and structural questions it raises are examined in the poem. Theoretical consideration of the genre and poetics will also be taken into account.
Keywords: recontextualization, tropes, paradox, dramatic monologue; Endre Ady; recontextualization; tropes; paradox; dramatic monologue